Modelling and Optimization of Wave Energy Converters - Ning, Dezhi; Ding, Boyin (Taylor & Francis, 2022)
Wave energy offers a promising renewable energy source. This guide presents numerical modelling and optimisation methods for the development of wave energy converter technologies, from principles to applications. It covers oscillating water column technologies, theoretical wave power absorption, heaving point absorbers in single and multi-mode degrees of freedom, and the relatively hitherto unexplored topic of wave energy harvesting farms. It can be used as a specialist student textbook as well as a reference book for the design of wave energy harvesting systems, across a broad range of disciplines, including renewable energy, marine engineering, infrastructure engineering, hydrodynamics, ocean science, and mechatronics engineering. The Open Access version of this book, available at https://www.routledge.com/ has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.